피나무의 임지생산력지수 및 임분수확모델 개발 - 김소라; Sora Kim; 임종수; Jongsu Yim; 이선정; Sunjung Lee; 송정은; Jungeun Song; 이혜림; Hyelim Lee; 손영모; Yeongmo Son (한국산림과학회지, 2023)
본 연구는 국가산림자원조사 자료를 활용하여 피나무림의 임지생산력지수와 수확예측모델을 도출하기 위하여 수행되었다. 피나무의 임지생산력을 알 수 있는 지위지수는 Schumacher 모델로서 파라미터를 도출하였으며, 이 결과로서 지위지수분류곡선도를 작성하였다. 국내 피나무림 지위지수 분포는 8~16 범위에 있는 것으로 나타났다. 임령을 설명변수로하여 흉고직경과 수고를 추정하는 생장모델은 Chapman-Richards 모델과 Weibull 모델을 이용하여 각각 도출하였다. 추정 모델의 적합도는 각각 0.32, 0.11로 나타나 일반적으로 볼 때 낮은 값이었으나, 추정식의 잔차가 “0”을 중심으로 고르게 분포하여 식을 적용하는데는 문제가 없을 것으로 판단되었다. 피나무림의 임분축적 변화에는 흉고단면적과 지위지수가 가장 큰 영향을 미치는 것으로 나타났다. 이 두 가지 인자를 적용시켜 피나무림의 수확모델을 도출하였으며, 모델에 대한 설명력은 약 94%로 높게 나타났다. 그리고 이들 수확모델의 잔차에 대한 정규성 및 자기상관 등에 대해서도 검증한 결과 문제가 없는 것으로 나타났다. 최종적으로 피나무림의 생장모델과 수확모델을 이용하여 임시로 활용할 수 있는 임분수확표를 제작하였으며, 이 자료에 의하면 피나무림이 70년생이 될 때, ha당 축적은 약 208 m 3 이 될 것으로 예측되었다. 본 연구의 결과가 밀원자원 및 목재로서 활용가치가 높은 피나무림에 대한 경영의사결정에 도움이 되기를 기대한다. This study aimed to use national forest inventory data to develop a forest productivity index and yield prediction model of a Tilia amurensis stand. The site index displaying the forest productivity of the Tilia amurensis stand was developed as a Schumacher model, and the site index classification curve was generated from the model results; its distribution growth in Korea ranged from 8-16. The growth model using age as an independent variable for breast height and height diameter estimation was derived from the Chapman-Richards and Weibull model. The Fitness Indices of the estimation models were 0.32 and 0.11, respectively, which were generally low values, but the estimation-equation residuals were evenly distributed around 0, so we judged that there would be no issue in applying the equation. The stand basal area and site index of the Tilia amurensis stand had the greatest effect on the stand-volume change. These two factors were used to derive the Tilia amurensis stand yield model, and the model’s determination coefficient was approximately 94%. After verifying the residual normality of the equation and autocorrelation of the growth factors in the yield model, no particular problems were observed. Finally, the growth and yield models of the Tilia amurensis stand were used to produce the makeshift stand yield table. According to this table, when the Tilia amurensis stand is 70 years old, the estimated stand-volume per hectare would be approximately 208 m 3 . It is expected that these study results will be helpful for decision-making of Tilia amurensis stands management, which have high value as a forest resource for honey and timber.